Efeitos do exercício físico e da Terapia Estrogênica sobre a reatividade vascular de aorta de ratas espontaneamente hipertensas Ovariectomizadas: papel do Sistema Renina-angiotensina - Endlich, Patrick Wander (2013)
Cardiovascular diseases are the major source of morbidity and mortality in most industrialized countries including in postmenopausal women, period characterized by a decrease in the estrogens production. Renin Angiotensin System (RAS) has been highlighted as a major mediator in the pathophysiology of many diseases, such as hypertension. Experimental and clinical studies showed upregulation of RAS after menopause. Although many experimental works report beneficial effects of hormonal replacement with estrogens, mainly 17β-Estradiol (E2), in the reduction of the risk to develop cardiovascular diseases, the results of clinical trials are so far to be conclusive. In this context, lifestyle modifications are necessary as the incorporation of regular physical training. Many studies have appointed that physical training can influence positively on the main cardiovascular risk factors. The aim of this study was to analyze the effects of chronic swimming training and estrogen therapy on vascular reactivity of aorta rings in ovariectomized spontaneously hypertensive rats (SHR) ovariectomized rats and the expression of RAS components in aorta. The animals were divided into five groups as following: Sham (S), Ovariectomized (OVX), ovariectomized treated with E2 (OTE2), ovariectomized+swimming (ON) and ovariectomized treated with E2 plus swimming (OE2+N). E2 replacement was performed by s.c. injection containing 5 µg of 17β-Estradiol, three times a week. Swimming training was conducted by sixty minutes daily in a continuous way and five times per week. Both, training and E2 therapy started seven days after ovariectomy and lasted eight weeks. Forty eight hours after the last treatment and/or training session, the animals had the systolic blood pressure measured, then were sacrificed and blood was collected to measure Angiotensin II plasma levels by radioimmunoassay (RIA)and to carry out two different protocols of analysis. For the functional study with aortic rings we evaluated the response to Ang II and Angiotensin-(1- 7) and the analysis of RAS proteins expression were made by Western Blotting method, which was performed in aorta artery. The results demonstrated that both exercise and E2 increased Ang II plasma levels. However, the systolic blood pressure was attenuated by treatments. The OVX group showed increase in the constrictor response to Ang II and decrease dilatator response to Ang-(1- 7), that was reverted by swimming training or E2 therapy associated to swimming. Moreover, ON and OE2+N groups showed increase in the AT2 and Mas receptor expression. On the other hand, the ON showed increase in the superoxide dismutase (SOD) anti-oxidant enzyme and only the groups treated with E2 showed increase on eNOS expression. Therefore, according to the results of the present study, we conclude that both, swimming training and E2 treatment may play a role in the cardioprotection and the chronic practice of physical exercise can be a feasible alternative in relation to estrogen therapy in post-menopausal women. However, the association between physical exercise and E2 therapy not promotes additional adaptations in the parameters analyzed.